The Effect Of Work Motivation On Employee Performance At The Dairi Regency Regional Finance And Assets Agency - Octo Pantas Mulianto Gultom; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study is a type of causal associative quantitative research that aims to analyze the relationship between two independent (exogenous) variables and their influence on bound variables. This research was conducted at the Dairi Regency Regional Finance and Assets Agency, with a population of 45 employees. The sampling technique used is saturated sampling, where all members of the population are sampled. Data was obtained through questionnaires distributed to all employees from various divisions. The results of the study show that work motivation has a positive and significant influence on employee performance, as evidenced by a calculated t value of 8.688 which is greater than the t table of 2.01669, and a significance value of 0.000 which is smaller than 0.05. This indicates that there is a significant positive influence between work motivation and employee performance at the Dairi Regency Regional Finance and Assets Agency. A regression coefficient of 1.368 indicates that every one-point increase in work motivation will lead to an increase of 1.368 points in employee performance, assuming the other variables are fixed. In addition, the results of the determination coefficient analysis showed an Adjusted R Square value of 0.637 or 63.70%, which indicates that work motivation has a considerable influence on employee performance. As many as 36.30% of employee performance is influenced by other factors that have not been researched in this study. Overall, this study concludes that increasing work motivation can contribute significantly to improving employee performance in the Dairi Regency Regional Finance and Assets Agency.